Soutenir l’autonomisation des adolescent·e·s et des jeunes adultes atteint·e·s de cancer : savoirs « psy » et travail de normalisation - Thibaud Pombet (Association Anthropologie Médicale Appliquée au Développement et à la Santé, 2021)
Since 2008, new services have been developed in France to provide medical and psychosocial care for “adolescents and young adults” (AJAs, aged 15 to 25) with cancer. In this context, this article examines the autonomy support practices put into place for these young patients between adolescence and adulthood. Fieldwork was carried out over a period of two and a half years, including fifty interviews conducted with young people and caregivers, as well as time spent observing them in care services and during professional training. The article shows that the model of support for the autonomy of AJAs with cancer is framed not only by the organizational divide between pediatric and adult medicine, but also the training courses for caregivers that transmit “psychological” knowledge about adolescence to support the work of normalizing young patients. The article then analyzes the effects of these “psych” knowledge behaviors in the AJA services and reports on the relationship that the professionals in the services have with this knowledge.